Sex and Gender Differences in Acute Pediatric Diarrhea: A Secondary Analysis of the DHAKA Study - Angela F. Jarman; Sara E. Long; Sarah E. Robertson; Sabiha Nasrin; Nur Haque Alam; Alyson J. McGregor; Adam C. Levine (Springer, 2018)
Pediatric diarrheal disease is a significant source of morbidity and mortality in the developing world. While several studies have demonstrated an increased incidence of diarrheal illness in boys compared with girls in low- and middle-income countries (LMIC), the reasons for this difference are unclear. This secondary analysis of the dehydration: assessing kids accurately (DHAKA) derivation and validation studies included children aged <5 years old with acute diarrhea in Dhaka, Bangladesh. The dehydration status was established by percentage weight change with rehydration. Multivariable regression was used to compare percent dehydration, while controlling for differences in age and nutritional status. In this cohort, a total of 1396 children were analyzed; 785 were male (56.2%) and 611 were female (43.8%). Girls presenting with diarrhea were older than boys (median age 17 months vs. 15 months, p = 0.02) and had significantly more malnutrition than boys, even when controlled for age (mean mid-upper arm circumference 134.2 mm vs. 136.4 mm, p < 0.01). The mean percent dehydration did not differ between boys and girls after controlling for age and nutrition status (p = 0.25). Although girls did have higher rates of malnutrition than boys, measures of diarrhea severity were similar between the two groups, arguing against a cultural bias in care-seeking behavior that favors boys